PENGARUH GOOD CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, LEVERAGE DAN PROFITABILITAS PADA TAX AVOIDANCE - Praditasari, Ayu; Setiawan, Putu Ery (E-Jurnal Akuntansi, 2017)
Tax avoidance is an attempt to reduce the amount of tax payable by exploiting loopholes contained in the applicable tax regulations. This study aimed to examine the effect of good corporate governance, size of the company, leverage, and profitability to tax avoidance. Good corporate governance components used in this study are institusional ownership, independent commissioner, and audit committee. This study focused on property and real estate companies listed in Indonesia Stock Exchange (BEI) in period 2011-2015. Number of observations is 165 samples obtained by the nonprobability sampling method and purposive sampling technique. The analysis technique used in this research is multiple linear regression analysis. The analysis showed that institusional ownership, audit committee, and size of the company have negative effect to tax avoidance as well as leverage and probability have positive effect to tax avoidance. The analysis also showed that the independent commissioner has no effect to tax avoidance .
Keywords: tax avoidance, good corporate governance, size of the company, leverage, profitability.